Limitations of Patients’ Communication with Mechanically Ventilated Patients: A Scoping Review - Widaryati Widaryati; Suhartini Ismail; Retnaningsih Retnaningsih; Ani Margawati; Muhammad Arsyad Subu (Indonesian Contemporary Nursing Journal (ICON Journal), 2026)
Aims: This review aimed to examine the effects of communication barriers, identify effective communication strategies, and determine appropriate interaction content for patients receiving mechanical ventilation. Methods: A scoping review approach was conducted using four databases: EBSCOhost, Elsevier, PubMed, and ProQuest, selected for their extensive health-related collections. Eligible studies were published between 2015 and 2025, written in English, and utilized quantitative or qualitative designs. The search incorporated keywords related to communication barriers, ventilated patients, intensive care, and critical care. Data was synthesized through systematic collation, summarization, and reporting. Results: Of 1,239 records identified, 20 studies met the inclusion criteria. Findings indicated that communication challenges affected patients, nurses, and family members, with consequences categorized as psychological and care-related impacts. Two primary communication approaches were identified: unaided and aided methods, with aided strategies further divided into low-technology and high-technology tools. Communication content clustered into three domains: expressing patient needs and desires, conveying complaints, and facilitating care-related interactions. Conclusion: Communication barriers significantly influence the well-being of patients, nurses, and families in intensive care settings. Both unaided and aided communication strategies can enhance interactions with mechanically ventilated patients. Structured communication focusing on patient needs and desires, concerns, and caregiving elements is essential to promote care quality and support patient well-being.